Combating covid-19 : our management at the campus level - Abd Rahman, Mohd Aizuddin; Mohammad Aidid, Edre; Ismail, Soraya; Saharudin, Shahida; Mustapar, Nurulhasanah (2022)
In Malaysia, Covid-19 has caused severe morbidity and mortality. Most people have been affected, including the university community. The spread of the virus has put the campus in peril. Covid-19 Kulliyyah (Faculty) Task Force was established to deal with covid-19 issues at our level. After the establishment of the task force, we faced difficulties in managing the students manually, especially in terms of contract tracing.